1996
DOI: 10.1021/jo951716t
|View full text |Cite
|
Sign up to set email alerts
|

Further Pseudopericyclic Reactions:  An ab Initio Study of the Conformations and Reactions of 5-Oxo-2,4-pentadienal and Related Molecules

Abstract: It has been proposed that all pseudopericyclic reactions are allowed, regardless of the number of electrons involved. 5-Oxo-2,4-pentadienal (1) is a vinylog of formylketene, and thus its reactions provide a test of this proposal. Ab initio (MP4(full, SDQ)/D95**//MP2/6-31G* + ZPE) calculations were carried out on all the conformations and several reactions of 1, as well as related systems. One of the eight possible conformations of 1 (zZz1) does not exist, but closes without a barrier, via a pseudopericyclic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
85
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 52 publications
16
85
0
Order By: Relevance
“…Electrocyclic ring opening (ERO) of pyrone has been found to be pseudeopericyclic by Birney and coworkers 27 and later Rodríguez and coworkers 28 have confirmed this by using NBO analysis. We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones.…”
Section: Introductionmentioning
confidence: 89%
“…Electrocyclic ring opening (ERO) of pyrone has been found to be pseudeopericyclic by Birney and coworkers 27 and later Rodríguez and coworkers 28 have confirmed this by using NBO analysis. We [29][30] have studied the thermolysis of 2-pyrone and 6-halo-2-pyrone and have found that fluorine substitution substantially altered the potential energy surface for ERO, sigmatropic rearrangement and electrocyclic ring closing (ERC) of pyrones.…”
Section: Introductionmentioning
confidence: 89%
“…18 Geometry optimizations have been carried out at MP2 level with 6-31g(d) basis-set because (i) MP2 gives fairly a good geometry and energy parameters of molecules in the ground state, 19 (ii) electron correlation is important in cases where intramolecular proton shifts are considered. 2,13 The minima have all real frequencies while TSs (Transition states) have a single imaginary frequency and the animation of this imaginary frequency has confirmed the transition states. Free energies have been calculated from thermochemical parameters obtained from frequency calculations.…”
Section: Methodsmentioning
confidence: 74%
“…This ketene aldehyde intermediate, a vinylog of well studied α-oxoketenes 3−12 resembles the α-oxoketenes in having a pseudopericyclic ring closure and sigmatropic hydrogen shift characterized by a planar or near planar transition state. 2 Later on Reva et al 13 have explored the whole pathway of rearrangement of pyrathione to thiapyrone. Recently, Alajarin and coworkers 14 have studied the migratory aptitude of halogens and other electron donor groups during the conversion of ketenimines into quinoline4 (3H)-ones.…”
Section: Introductionmentioning
confidence: 99%
“…In hindsight, one can perhaps rationalize the unexpected facility of the rearrangement by identifying it as a pseudopericyclic 17 rather than a truly pericyclic reaction. The hypothetical electron transfers in the pseudopericyclic process are shown schematically in Figure 4.…”
Section: Discovery Of Apparent Nonstatistical Dynamics For a Wolff Rementioning
confidence: 99%